Pemberdayaan Ibu tentang Pijat Bayi untuk Kesejahteraan Bayi dan Balita di Kelurahan Paal Lima Kota Jambi - Astria, Niki; Marlin, Diane; Rahmawati, Dwi; Kurniasari, Lidya; Anggraini, Putri Dewi (Jurnal Abdimas Kesehatan (JAK), 2025)
Baby massage is one form of early stimulation that can improve the overall health and well-being of the baby, both from the physical, emotional, and motor development aspects. However, the knowledge and skills of the mother in doing baby massage are still limited, especially in urban communities such as Paal Lima Village, Jambi City. This devotional activity aims to empower mothers through community-based education on appropriate and safe infant massage techniques. Methods of implementation include counseling, direct demonstrations, and interactive training focused on the active participation of the participants’ mothers. Evaluation results showed a significant improvement in the mother's knowledge and skills regarding baby massage, as well as increased confidence in caring for the baby. This activity shows that community-based education can be an effective strategy in increasing the capacity of parents to support optimal infant growth. Empowerment of the mother through simple interventions such as infant massage training contributes directly to the improvement of early childhood well-being at the community level.